The local historian and the press - M.D. Moore (Contree, 2024)
This article examines to what extent some 19th century country town newspapers of the Eastern Cape frontier can be used by the local historian. An analysis of editorials found certain common policies and ideas espoused by the editors, e.g. the pursuit of objectivity and the view that the local newspaper was a channel of communication between the government and the population, a kind of forum for the expression of public opinion. In spite of their declared aim of impartiality, many of these newspapers were however established either with the express purpose of furthering the interests of a particular group of they gradually became closely associated with certain sections of the community. Matters of local importance in these papers include local government, the administration of justice, social problems, economic and agricultural development, and the colonists' attitude towards race, as expressed in their fears for the security of their persons and stock. These are all matters which provide the local historian with valuable information which is otherwise unavailable in any other source. From these newspapers the local historian is often able to obtain a clear indication of what to look for in official documents kept in the archival depots, which can be of great practical value in terms of time and money.